(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study identified the effectiveness of Curfew Hours in Barangay Payatas Quezon City. It was focused on the demographic profile, the factors that influence the effectiveness of curfew hours, and the problems encountered by Barangay Payatas Quezon City. The findings of the study revealed that most of the respondents were thirty (30) years old and above, with a frequency of thirty-two (32) or 45.71%. The majority of the respondents were male, with a frequency of forty-six (46) or 65.71%. On the factors that influence the effectiveness of curfew hours, the study showed that crime rate was the highest factor, with a weighted mean of 3.52 and an interpretation of “strongly agree.” On the other hand, the study showed that the rank one problem encountered by the Barangay Payatas was the rude behavior of the community when violating curfew hours or being detained. Lastly, the study showed that the measures that should be proposed to address the problem encountered were the curfew advisory board with a weighted mean of 3.74 and verbal interpretation of “strongly agree.” As a result of the research, it was suggested that the Barangay Payatas should explore the potential role of community-based interventions that can improve the relationship between authorities and the community, such as education programs, community awareness, and assembly between families and barangay personnel to support family needs. In addition, the Barangay Payatas should conduct a more comprehensive study on curfew hours in regard to the economic progress in the community. Finally, examine the workforce and the strategic plan for implementing curfew hours.